Sources of support and expatriation: A multiple stakeholder perspective of expatriate adjustment and performance in Malaysia - Abdul Malek, Marlin Marissa (Taylor & Francis Group, 2015)
This research tests the role of perceived support from multinational corporations and host-country nationals for the adjustment of expatriates and their spouses while on international assignments.The investigation is carried out with matched data from 134 expatriates and their spouses based in foreign multinationals in Malaysia.The results highlight the different reliance on support providers that expatriates and their accompanying spouses found beneficial for acclimatizing to the host-country environment.Improved adjustment in turn was found to have positive effects on expatriates' performance. The research findings have implications for both international human resource management researchers and practitioners.